2013
DOI: 10.3409/fb61_1-2.87
|View full text |Cite
|
Sign up to set email alerts
|

Motility Parameters and Intracellular ATP Content of Rabbit Spermatozoa Stored for 3 Days at 15°C

Abstract: The effect of semen storage duration on motility parameters and ATP content of rabbit spermatozoa were investigated. Ejaculates were collected from 9 New Zealand White male rabbits and diluted with a commercial rabbit semen extender Galap. Semen was stored at 15 degrees C for 3 days. On each day of storage sperm motility and intracellular ATP content were evaluated. Sperm motility parameters were assessed using the computer-assisted sperm analysis (CASA) system and ATP content using the bioluminescence method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
(16 reference statements)
2
8
0
Order By: Relevance
“…However, in both groups (Control and GnRH) significant changes in motility parameters (except VSL) and percentage of spermatozoa showing high MMP and ATP content were observed throughout 3 days of storage. According to our previous studies (Gogol andWierzchoś-Hilczer 2009, Gogol 2013) the most sensitive parameters of semen quality were motility (especially TMOT and PMOT) and ATP content of the spermatozoa. A small (but statistically significant) decrease in the percentage of spermatozoa with high MMP (7.6% in Control and 6.2% in GnRH group) may suggest that this parameter is less suitable for estimating the in vitro quality of stored rabbit spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in both groups (Control and GnRH) significant changes in motility parameters (except VSL) and percentage of spermatozoa showing high MMP and ATP content were observed throughout 3 days of storage. According to our previous studies (Gogol andWierzchoś-Hilczer 2009, Gogol 2013) the most sensitive parameters of semen quality were motility (especially TMOT and PMOT) and ATP content of the spermatozoa. A small (but statistically significant) decrease in the percentage of spermatozoa with high MMP (7.6% in Control and 6.2% in GnRH group) may suggest that this parameter is less suitable for estimating the in vitro quality of stored rabbit spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MMP and ATP content of spermatozoa, both considered as sensitive indicators of energy metabolism and motility (Marchetti et al 2004, Gogol 2013, were determined. The results show that addition of the GnRH analogue to the extender did not have any significant effect on sperm function, as measured by motility parameters, MMP and ATP content.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The availability of semen that can be stored for longer periods would allow an extension of the interval between semen collection and insemination of the females (Di Iorio et al 2014). Thus, enhancing AI performance in case of farms without male located far away from semen collection centres (Gogol, 2013). Previous researches showed that the fertilizing ability of rabbit spermatozoa was preserved for up to 48 h using chilled storage techniques (Roca et al 2000;L opez-Gatius et al 2005;Rosato & Iaffaldano 2011), thus enabling the transportation of superior genetics between nearby farms.…”
Section: Introductionmentioning
confidence: 99%